STUDENTS’ ATTITUDES TOWARDS LANGUAGES AND MAINTENANCE OF HERITAGE LANGUAGES: A CASE STUDY OF PAPUAN SENIOR HIGH SCHOOL STUDENTS - Kasih Elisabet Roostini; Christine Manara (Journal of English Language and Culture, 2021)
Language shift may lead to language investment, and it may also affect language heritage maintenance.  This case study aims to explore maintenance of language heritage among a group of Papuan students who are living in a school dormitory, away from their families. These 29 senior high school students are originally from different ethnic groups from several districts in  Papua. A questionnaire and a semi-structured interview video-recorded for data collection were employed to find out the students’ attitudes towards languages and maintenance of heritage languages. The questionnaire was designed and developed by adapting the semi-structured interview questions designed by Berman et al. (2011). The data were analysed based on the aspects organised in the questionnaire and the results were compared with the findings of Berman et al.’s  (2011), Ehala and Niglas’s (2006), and Nguyen’s (2018) studies. The result shows that there has been a language shift among these adolescents. Living among a community that is totally different from theirs has driven them to adapt and accept the language used in the community. Technology exposure at school has also affected their perspectives towards their future, which motivates them to invest in other languages that they think are important for their future career. Their positive attitudes towards other languages do not discourage them from maintaining their heritage language, as they perceive the use of heritage language as a way to stay connected with their own culture.